Evaluating the thermal insulation properties of sustainable building materials in Southern Algeria: A study on plaster and palm fibres - Rachedi, Mokhtar; Kriker, Abdelouahed (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
This research addresses the critical need to develop environmentally friendly building materials with effective insulation properties in Southern Algeria, a region increasingly affected by extreme natural phenomena such as intense heat. By exploring the potential of plaster, known for its excellent insulation characteristics, and palm fibres, a sustainable alternative to synthetic fibres, this study offers a promising future for the construction industry in the region. Plaster composites reinforced with 10 mm palm fibres were developed at 2%, 4%, and 6% fibre ratios and water-to-plaster (W/P) ratios of 0.8, 1, and 1.5. After 28 days, physical, mechanical, and thermal properties were evaluated. The results revealed that composites with 6% fibre and a 1.5 W/P ratio exhibited favourable physical properties, particularly a low density of 0.88 g/cm³, making them lightweight. Although the compressive strength decreased to 5.23 MPa with increasing fibre and water content, it remained within acceptable limits. The thermal conductivity decreased to 0.19 W/mK, and the specific heat increased to 1012.17 J/kg·K, highlighting the material’s effectiveness as an insulator. This study demonstrates the potential of local, sustainable building materials, positioning date palm fibre-reinforced plaster composites as a viable solution for sustainable construction. The findings encourage further research on optimising these composites for broader environmentally conscious construction applications.